PENGARUH STRATEGI PEMBELAJARAN BERBASIS PROYEK (PROJECT- BASED LEARNING) PADA MOTIVASI BELAJAR MAHASISWA PENDIDIKAN TEKNIK BANGUNAN - Tiara Riyanti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
A popular teaching paradigm in various fields of education, including construction technique education, is the project-based learning strategy. The purpose of this study is to assess the impact of a project-based learning strategy on student motivation for construction technique instruction. The method of study that is employed is literature review, which involves gathering information from several reliable sources, such as academic journals and books. According to the study's findings, learning strategies based on projects have a positive impact on students' motivation to learn construction technique. This strategy can increase commitment and discipline, academic discipline, the desire to learn and understand, self-awareness and self- doubt, intrinsic motivation, teamwork and collaboration, problem-solving skills, communication skills, and critical thinking capacity. Proyek-based learning strategies have a great potential to improve learning outcomes and raise student quality.